Association of genomic profiles and survival in early onset and screening‐age colorectal cancer patients with liver metastases resected over 15 years. Issue 5 (23rd January 2022) - Narayan, Raja R.; Aveson, Victoria G.; Chou, Joanne F.; Walch, Henry S.; Sanchez‐Vega, Francisco; Santos Fernandes, Gustavo Dos; Balachandran, Vinod P.; D'Angelica, Michael I.; Drebin, Jeffrey A.; Jarnagin, William R.; Wei, Alice C.; Cercek, Andrea; et al.
Abstract: Background: This study explores whether genomic profiles of colorectal liver metastasis (CRLM) patients with early onset (EO, < 50 years old) and screening age (SA) primary diagnosis are associated with overall survival (OS). Methods: All patients undergoing hepatectomy between 2002 and 2017 were identified and tumor specimens with next‐generation sequencing data were cataloged. Gene and signaling‐level alterations were checked for association with OS from primary diagnosis accommodating for left‐truncated survival. Results: Of 1822 patients, 333 were sequenced–127 (38%) EO‐CRLM and 206 (62%) SA‐CRLM patients. More aggressive features presented in EO‐CRLM patients–synchronous metastatic presentation (83% vs. 75%, p < 0.001) and primary node‐positive disease (71% vs. 61%, p < 0.001). The median OS from primary diagnosis was 11.8 years (95% confidence interval = 7.94‐NA). Five‐year OS did not differ by age ( p = 0.702). On multivariable analysis, altered APC (EO‐CRLM: [hazard ratio [HR] = 0.37, p = 0.018] vs. SA‐CRLM:[HR = 0.61, p = 0.260]), BRAF (EO‐CRLM:[HR = 4.38, p = 0.007] vs. SA‐CRLM:[HR = 4.78, p = 0.032]), and RAS‐ TP53 (EO‐CRLM:[HR = 2.82, p = 0.011] vs. SA‐CRLM:[HR = 2.35, p = 0.003]) associated with OS. Conclusions: Despite bearing more aggressive features, EO‐CRLM patients had similar genomic profiles and survival as SA‐CRLM patients. Better performance status in younger patients leading to increased treatment tolerance may partly explain this. As screening and treatment strategies from older patients are applied to younger patients, genomic predictors of biology identified historically in older cohorts could apply to EO patients.